Sensors and Techniques for 3D Object Modeling in Underwater Environments (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Water covers approximately 71% of the planet's surface and human activities have been relying on it since remote times. Many traces of these exist under the "zero level" and will continue to exist in the future. Measuring, positioning, and mapping objects under water have experienced very significant modifications, brought about by advances in technology and also by changed requirements, demands for new products, introduction of new tools, and the modification of existing equipment. The exploration, documentation, and recording of underwater environments remains a difficult task, and is sometimes still unsolved. The research, design, and development of techniques and procedures for correctly validating underwater environments are more than ever important. This Special Issue originates from the ISPRS/CIPA Workshop "UNDERWATER 3D RECORDING & MODELING-Experiences in Data Acquisition, Calibration, Orientation, Modelling & Accuracy Assessment" (http://3dom.fbk.eu/files/underwater/index.html) and will accept improved and extended selected papers derived from the workshop's proceedings, as well as new contributions from international colleagues. We invite you to submit articles on the following topics: Underwater/Multi-media photogrammetry Underwater platforms (ROV, AUV, robot, etc.) Characterization of underwater passive and active sensors Underwater navigation and positioning Underwater metrology and inspections Geometric modeling in multi-media photogrammetry Accuracy requirement and assessment in underwater 3D applications Restoration, enhancement and processing of underwater images 3D bathymetry techniques Data processing and underwater 3D modeling Sensors for marine biology and water pollution Multi-sensor integration